A Critical Analysis of Immigrant Advocacy Tropes: How Popular Discourse Weakens Solidarity and Prevents Broad, Sustainable Justice - Lara, Dulcinea (Social justice, 2009)
This article discusses the themes, logic, and values found in rhetorical figures of speech that are associated with national, local, and private discussions that support immigration and how these figures of speech and their meanings are used to fight anti-immigrant discrimination and to influence public policy favoring immigrants. The article notes that collective behavior and social movement scholars have identified many factors that contribute to the evolution of collective action and social movement organization. The article looks at some of these factors and how they affect immigration advocacy.